2023
DOI: 10.1002/net.22144
|View full text |Cite
|
Sign up to set email alerts
|

Two extended formulations for the virtual network function placement and routing problem

Abstract: Given a bi‐directed graph modeling a telecommunication network, and a set of origin‐destination pairs representing traffic requests (commodities) along with their associated Service Function Chains (SFCs), the Virtual Network Function Placement and Routing Problem (VNFPRP) aims to find, for each commodity, one latency‐constrained routing path that visits the required Virtual Network Functions in a specific order. The function installation costs together with the node activation costs have to be minimized. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Research [11] presented the VNF service function chains (SFCs) placement problem with various algorithms; this research helped us to build the service chain of VNF, but they did not provide more information about VNF cost. There are many types of research such as [6], [12]- [14] that present various ways for VNF placement latency, energy consumption, and optimization of resources; thus, these show the importance of VNF resources. However, they did not consider software costs.…”
Section: A) Vnf Resources Allocation In Generalmentioning
confidence: 99%
“…Research [11] presented the VNF service function chains (SFCs) placement problem with various algorithms; this research helped us to build the service chain of VNF, but they did not provide more information about VNF cost. There are many types of research such as [6], [12]- [14] that present various ways for VNF placement latency, energy consumption, and optimization of resources; thus, these show the importance of VNF resources. However, they did not consider software costs.…”
Section: A) Vnf Resources Allocation In Generalmentioning
confidence: 99%
“…From the literature review, we observed that linear programming, especially ILP [25,46,55,61,62] and MILP [21,23,24,47,63], is the most commonly used technique. However, only a small subset of studies applies non-linear programming methods [102,105] to formulate the problem.…”
Section: Placement Methodsmentioning
confidence: 99%
“…Mouaci et al [23] Song et al [56] investigate the resource-efficient VNFP problem to minimize computing and communication (bandwidth) resources. An ILP and a heuristic are provided based on the hidden Markov model.…”
Section: Single-branch Sfc Placementmentioning
confidence: 99%
See 2 more Smart Citations